2017
DOI: 10.1111/aogs.13087
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during pregnancy and risk of preterm birth in overweight and obese women: a systematic review and meta‐analysis of randomized controlled trials

Abstract: Introduction. The incidence of overweight and obesity in pregnancy has risen significantly in the last decades. Overweight and obesity have been shown to increase the risk for some adverse obstetric outcomes. Lifestyle interventions, such as diet, physical activity and behavior changes, may reduce these risks by promoting weight loss and/or preventing excessive weight gain. The possible impact of exercise on the risk of preterm birth (PTB) in overweight or obese women is controversial. Therefore, the aim of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
97
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 22 publications
5
97
1
7
Order By: Relevance
“…As demonstrated in previous studies that investigated other interventions aimed at reducing BW in obese pregnant women, including diet and lifestyle interventions, we showed no significant effect for this outcome.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As demonstrated in previous studies that investigated other interventions aimed at reducing BW in obese pregnant women, including diet and lifestyle interventions, we showed no significant effect for this outcome.…”
Section: Discussionsupporting
confidence: 72%
“…This meta-analysis of two RCTs including 849 obese pregnant women showed that the use of metformin in this population was associated with a significant reduction in MWG. Metformin was also associated with a significantly lower incidence of PE and admission to the NICU, while no differences were found with the As demonstrated in previous studies that investigated other interventions aimed at reducing BW in obese pregnant women, including diet and lifestyle interventions, [23][24][25][26] we showed no significant effect for this outcome.…”
Section: Discussionsupporting
confidence: 43%
“…Di Mascio et al in a recent meta‐analysis of nine studies including 2059 women, showed that in low‐risk uncomplicated normal‐weight singleton gestations, aerobic exercise can be safely performed, as this is not associated with an increased risk of preterm birth or with a reduction in mean gestational age at delivery but is associated with higher chance of vaginal delivery and lower rate of cesarean delivery as well as a lower incidence of gestational diabetes mellitus . Another meta‐analysis by Magro‐Malosso et al found that overweight or obese women with singleton pregnancy who were randomized to 30–60 min three to seven times per week during pregnancy had a reduced risk of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Trials in women treated only with exercise or diet at the time of randomization were excluded. Exercise in pregnancy has been shown to reduce the risk of diabetes in both normal‐weight and overweight and obese women , as well as to improve pregnancy outcome in those with GDM .…”
Section: Discussionmentioning
confidence: 99%